THE ROLE OF DIGITAL MARKETING FOR THE INDONESIAN INCLUSIVE BOARDING SCHOOL - Awang Saputra; Muhamad Fauzi (International Journal of Innovative Technologies in Social Science, 2022)
Providing wholehearted service to students with special needs is a noble challenge, and the presence of the extraordinary school is an equal education effort in Indonesia. This study aims to determine digital marketing management in inclusive education. The research method is qualitative with the type of literature study. The study found that digital marketing is coordinated by a public relations representative, involving all teachers so that they are not seen as inclusive and equal to other schools. Students with special needs who live in boarding schools receive more religious lessons and skills assignments as additional activities in addition to regular study. Parents feel calm and comfortable if their children participate in activities in boarding schools so that they can interact and communicate more with their friends. Inclusive education services demonstrate independence and build community trust to meet student needs. Muhammadiyah association can provide educational institutions with the best services for students with special needs is a command in Islam.